Evaluating pathogen reduction of Trypanosoma cruzi with riboflavin and ultraviolet light for whole blood - Tonnetti, Laura; Thorp, Aaron M.; Reddy, Heather L.; Keil, Shawn D.; Goodrich, Raymond P.; Leiby, David A. (Transfusion (Philadelphia, Pa.), 2012)
BACKGROUND: Trypanosoma cruzi, the protozoan parasitic agent of Chagas disease, can be transmitted by blood transfusion. In 2007, most US blood banks started screening blood donations for T. cruzi, but the cost and perceived need of the test have been the subject of ongoing discussion. In this study, we evaluated the ability of the Mirasol System (CaridianBCT), which uses riboflavin (RB) and ultraviolet light to inactivate pathogens, to reduce the levels of infectious T. cruzi in whole blood (WB). STUDY DESIGN AND METHODS: WB units were inoculated with 4, 40, 400, and 4000 trypomastigotes/mL. After addition of RB and illumination at various energy levels, the samples were tested for the presence of live parasites by hemoculture. RESULTS: All preillumination samples exhibited T. cruzi growth in hemoculture, while postillumination samples from units containing 4 and 40 trypomastigotes/mL showed no signs of viable parasites after 16 weeks of culture. In contrast, at both 400 and 4000 parasites/mL, two of the three units were positive for viable parasites. CONCLUSIONS: The total log reduction observed for T. cruzi was 3.5 log or greater, but less than 4.5 log. This level of reduction is likely to be orders of magnitude higher than what would be expected in a tainted blood donation, indicating that the Mirasol System could be effective at preventing transfusion of the causative agent of Chagas disease.